Kampen om den vestindiske salmebog 1850-1917 - Bach-Nielsen, Carsten (Kirkehistoriske Samlinger, 2007)
The island of St. Thomas in the West Indies was seized by the Danish West Indian Company in 1666. Lutheran pastors since then arrived in the island with Danish officials and settlers. Their task was to conduct services to the Lutheran inhabitants and to converse the indigenous people of the new territory. There was however no Indians left at the arrival of the Danes. Settlers from other European nations such as Brandenburg Calvinists soon arrived and it was agreed to establish religious freedom in the Danish island. With the massive import of slaves form Africa it was discussed whether they be converted to Christianity - and who was to do so. The Danish Church did not establish a mission to the slaves. It did not happen until 1732 as the Moravians were granted a mission privilege. The colony was extended with St. John and St. Croix and finally taken over by the Danish king in 1754. In 1757 the Lutheran Church of Denmark sent its first missionaries to compete with the Moravians’ mission. The Danish mission was not successful as the missionaries were not allowed to baptize and one of their main efforts was to teach the slaves Danish. The language of the slaves was Creole. During the 1760es the New Testament, a grammar, a catechism, and a hymn-book were translated and issued in this language. There is very little evidence to the assumption that E. Røring Wold published the earliest hymn-book. It seems likely that it was done by the missionary J.C. Kingo in 1770. New hymn-books were published in 1799 and in 1823. They were equals to official Danish hymn-books although of a considerably smaller size. The Litany contained prayers for the Danish king, the royal government, the governor, the mission, and the planters. The aim obviously was the subordination of the slaves. As a consequence of the British occupation of the islands from 1807 to 1815 the language shifted towards English. The islands were opened to a wider world, not least the United States. In Denmark the former West Indian pastor J. Klint Bagger translated a number of hymns into English. Together with hymns translated by pastor Tolderlund of St. Croix it became the first Danish-West Indian hymn-book in English in 1850. It was authorised by the Danish government in Copenhagen. In 1851 - three years after the Emancipation - the mission ran short of money. At that time all the former slaves had converted to some European confession. Normally hymn-books would have been paid and distributed by the Mission funds. Consequently the Lutheran congregations and their Sunday-schools began purchasing their hymn-books in Philadelphia, USA. They were granted the right to use the American Lutheran Hymnal in 1853, but it could not be authorized by the authorities in Copenhagen as it was not a Danish book. In 1872 Hymns, Liturgy, and Prayersfor the Use of The Evangelical Lutheran Church of The Danish Westindia Islands was printed and issued in Copenhagen. The hymns had been selected from the American hymnal by the pastors Lose and Willemoes. Only four translations of Danish hymns were found in it. The hymnal was reissued twice in 1880 and 1904. Pastor Lose in the 1880es was very eager to establish a supplement to the hymnal but failed due to the lack of interest of the Danish ecclesiastical authorities and the congregations in the Danish West Indies. His proposal was to select the best translations of Lutheran hymns from different American sources - and to find Danish tunes for them. His proposal was examined by the British professor George Stephens of Copenhagen who ridiculed the contents of the hymns as well as their American spelling! In 1902 the Danish parliament decided not to sell the islands to USA. Instead reforms and new capital was to modernize the forgotten islands. In Denmark a board of pastors and laymen, Den vestindiske Kirkesag, worked towards the elimination the old double standards between the white Danish and the coloured English congregationus. Actually the Lutheran Church of the Danish West Indies in 1907 was incorporated into the Danish State Church. The Danish pastors of the islands expressed the want of an entirely new hymnal. A proposal by the pastors Helweg-Larsen and Faber was sent to Copenhagen in 1914, but it was never published, as a treaty on the transfer of the islands to the US was signed in 1916 and sealed with a referendum in Denmark. At that time however Sankey’s international bestseller Sacred Songs and Hymns with its popular texts, sweet tunes, and low price had far superseded translations and collections of national hymns of insignificant European countries in the Caribbean context.